Pengembangan Sistem Ekowisata Candi Gedong Songo Di Kabupaten Semarang - Sulistyadi, Kohar (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
Ecotourism Gedong Songo administratively located in Semarang district and are planted strategically in the middle of Yogyakarta, Solo and Semarang known as (Joglosemar) which is easily accessible by road highway Semarang - Solo or Semarang - Yogyakarta. Gedong Songo Temple which is the Hindu religious shrine with dazzling panorama. Gedong Songo Temple was built during the enshrinement almost Dieng is considered the oldest Hindu temple in Central Java. Estimated Gedong Songo Temple made within century VII - IX AD. Gedong Songo enshrinement which is composed of nine groups of temples. (Songo means nine), but currently there are only five (5) groups of temples are still intact while the four (4) other temple has collapsed and only a foundation or the base, the temple was restored by the Dinas Purbakala. Sustainable management of ecotourism as environmentally sound tourism activities have a strong dependence on tourist visitation. To create the ideal conditions of each subsystem relationships and interdependency,Â  interacting with each other in ecotourism as one that is holistic, it encountered many difficulties because each subsystem are many who work on their own or individual. In order for the management of ecotourism can give hope many stakeholders, it is necessary to study a complete and comprehensive system, so that the potential of ecotourism Gedong Songo region capable of attracting tourists, able to provide economic growth, community participation, promote the advancement of education, local culture, and ongoing basis Keyword: Ecotourism culture, Gedong Songo, systems approach